The Effect of Marketing Mix and Reference Group on Chicken Nugget Preference Through Brand Image - Syaprudin, R.; Simanjuntak, Megawati; Heny Kuswanti Suwarsinah (Jurnal Manajemen dan Agribisnis, 2023)
Due to the increasingly fast-paced lifestyles and busy lives of urban citizens, the demand for chicken nuggets has continued to rise. This study aims to analyze the effect of the marketing mix (product, place, price, promotion) and the reference group on consumer preference for chicken nuggets through the brand image formed in the market. The respondents consisted of 251 individuals who were selected through voluntary sampling. These respondents were people who had consumed Fiesta and So Good brand chicken nuggets in the last three months. Data were collected through an online questionnaire and analyzed using descriptive and Structural Equation Modeling. The results for Fiesta show that place has a significant effect on brand image. Meanwhile, product, reference group, and brand image have a significant effect on brand preference. The results for Fiesta also indicate that brand image is an intervening variable. Therefore, this study concludes that place significantly affects brand preference through brand image. For So Good, the results show that place and promotion significantly affect brand image, but product, price, and reference group have no significant effect on brand image. Furthermore, product, reference group, and brand image significantly affect brand preference. The indirect effects of So Good's brand with brand image as an intervening variable indicate that place significantly affects brand preference through brand image.Keywords: brand image, chicken nugget, marketing mix, preference, the reference group